Taxation of individuals - Spilker, Brian C. (McGraw-Hill Irwin, 2011)
The basic approach to teaching taxation hasnt changed in decades. Todays student deserves a new approach. McGraw-Hills Taxation of Individuals is a bold and innovative new textbook thats already generating enthusiasm across the country. McGraw-Hills Taxation Series is designed to provide a unique, innovative, and engaging learning experience for students studying taxation. The breadth of the topical coverage, the storyline approach to presenting the material, the emphasis on the tax and nontax consequences of multiple parties involved in transactions, and the integration of financial and tax accounting topics make this book ideal for the modern tax curriculum